Analysis of Factors Affecting Magnetic Memory Time of CaCO3 Solutions Based on Orthogonal Experiment - Lv, Zhe; Liang, Yandong; Jia, Meng; Wang, Jianguo; Zhang, Xiuyu (Sensors and materials, 2020)
To investigate the effects of magnetic induction intensity, magnetic field treatment time, and solution concentration on the magnetic memory time of CaCO3 solution, an orthogonal experiment was carried out to establish a L16(45) orthogonal table, and 16 groups of experimental results were obtained on the basis of a self-made electromagnetic water treatment experimental platform. Range and variance analyses were carried out. Experimental results indicated that the main factor affecting the magnetic memory time of CaCO3 solution is the magnetic induction intensity and the effect is significant. The magnetic field treatment time and solution concentration have little effect on the magnetic memory time. In addition, optimum experimental conditions were obtained. When a CaCO3 solution of 2 mmol/L concentration was treated for 36 h with a magnetic induction intensity of 300 Gs, the longest magnetic memory time (about 5600 min) was observed. These research results provide the theoretical basis for the selection of subsequent experimental parameters.